Optical coherence tomography angiography and arterial hypertension: A role in identifying subclinical microvascular damage?. Issue 1 (January 2021) - Donati, Simone; Maresca, Andrea Maria; Cattaneo, Jennifer; Grossi, Alessandra; Mazzola, Marco; Caprani, Simona Maria; Premoli, Laura; Docchio, Franco; Rizzoni, Damiano; Guasti, Luigina; Azzolini, Claudio
Introduction: To evaluate retinal microvasculature modifications by means of optical coherence tomography angiography in human subjects diagnosed with arterial hypertension and to assess potential clinical relevance for early diagnosis. Methods: A cross-sectional study of 30 subjects affected by arterial hypertension compared to a matched cohort of healthy patients was conducted. Patients were evaluated by the Outpatient Clinic for Hypertension and the Retina Center, University of Insubria, Varese, Italy. Patients were divided into three groups: Group 1—healthy subjects, Group 2—patients first diagnosed with hypertension, and Group 3—patients with treated hypertension. Optical coherence tomography angiography was performed applying different analysis protocols for macula and optic disk, using an AngioVue OCTA System on an Optovue device. Morphological data were compared to and correlated with clinical vascular parameters, to evaluate preclinical microvascular damage. Results: A significant reduction in deep vascular layer density (Group 1: 59.2% ± 1.5% standard deviation; Group 2: 59.2% ± 2.2% standard deviation; Group 3: 57.8% ± 2.6% standard deviation; p < 0.05) as well as an enlargement of the deep foveal avascular zone area (Group 1: 0.34 ± 0.09 mm 2 ; Group 2: 0.36 ± 0.07 mm 2 ; Group 3: 0.39 ± 0.1 mm 2 ; p < 0.05) was measured in patients with first diagnosed hypertension and in treated patients compared to healthy subjects. We also observed a significant decrease in mean foveal choroidal thickness in affected patients compared to controls (Group 1: 319.68 ± 61.72 µm standard deviation; Group 2: 251.04 ± 63.1 µm standard deviation; Group 3: 262.65 ± 51.08 µm standard deviation; p < 0.05). Our preliminary data did not show a significant correlation with microalbuminuria levels. Discussion: Retinal vascular density showed pathological modifications between healthy subjects and hypertensive patients. These preliminary findings suggest that optical coherence tomography angiography may identify pathological markers of an early hypertensive damage and help monitor disease progression with potential therapeutic advantages.